The Effect of Health Promotion on the Compliance of Patients Taking Hypertension Medication at the Medan City Exemplary Health Center 2023 - Doloksaribu, Purnama; Nuraini, Nuraini; Asriwati, Asriwati (Universitas Ibn Khaldun Bogor, 2025)
Hypertension is one of the non-communicable diseases that is a very serious health problem today. Uncontrolled hypertension can lead to a 7 times greater chance of having a stroke, 6 times greater chance of developing congestive heart disease, and 3 times greater developing a heart attack. At the Teladan Health Center, there are still 36% of hypertension patients who have not been controlled, where data on the number of hypertension patients in 2021 is 842 people and in 2022 as many as 1162 people. Some of them are factors that affect non-adherence to taking medication, namely understanding of instructions, level of education, treatment, beliefs, attitudes, and personality as well as family support, The purpose of this study is to determine the influence of health promotion on knowledge, attitudes and actions with adherence to taking hypertension medication. This study uses a combination of quantitative and qualitative methods (mixed method) with a sequential explanatory approach is a combined research method that uses data collection and quantitative analysis in the first stage and followed by qualitative data collection and analysis in the second stage, in order to strengthen the results of quantitative research conducted in the first stage. The research was conducted by 51 people in the experimental group and 51 people in the control group, in the qualitative research of informants as many as 8 people where 3 people were the main informants, 3 people were supporting informants, and 2 people were key informants, in quantitative research it was carried out by univariate analysis and bivariate analysis of the test which was carried out in the quantitative research of independent samples test T-Test, while in qualitative research data processing was carried out by means of data reduction, Data presentation, and drawing conclusions The test used in this study is a data credibility test, which is carried out using source triangulation techniques, discussions with peers and membercheck. Source triangulation is a technique for collecting information from various sources. The results of the study showed that there was an influence of health promotion on knowledge, attitudes, and actions with medication adherence. In groups Control also there is an average change for theHUAN of 0.45 with a p-value of 0.004. Mean value of attitude on results Post Test The experimental group experienced an increase with an average change of 2.78. In the control group, there was also an average difference of 0.33 and a sig. p-value 0.010 < 0.05 . Mean value of action on results Pre Test The experimental group also experienced an increase with an average change of 3.04. For actions in the experimental group, the SIG value was shown. p-value 0.000 < 0.05. In the control group the mean value for the action at the time Pre Test also experienced an increase of 0.75 but with a p-value of 0.000 < 0.05 means that there is a significant difference after health promotion.and there is a reinforcing factor, namely family support, support of health workers which can increase compliance with taking hypertension medication. The conclusion of this study is that there is an increase in adherence to taking hypertension medication after health promotion and there are driving factors that affect adherence to taking hypertension medication, namely the support from family and support from health workers, in addition to the factor of affordability of access to health services. Using the flip sheet media as a promotional medium about medication adherence and improving health services, especially for hypertension patients who are generally in the elderly.